Lung Ultrasound Combined With Procalcitonin for a Diagnosis of Ventilator-Associated Pneumonia - Zhou, Juandi; Song, Jia; Gong, Shijin; Hu, Weihang; Wang, Minjia; Xiao, Aibing; Zhang, Cong; Dong, Zhouzhou (Respiratory care, 2019)
Lung ultrasound is a valuable imaging tool in the diagnosis of community-acquired pneumonia. However, its diagnostic accuracy in ventilator-associated pneumonia (VAP) has not been fully investigated. The aim of this study was to evaluate the diagnostic performance of the combination of a lung ultrasound with procalcitonin (PCT) in mechanically ventilated subjects with symptoms suggestive of pneumonia. A prospective study of 124 subjects with suspected VAP in 2 multidisciplinary ICUs was conducted between December 2016 and October 2017. Lower respiratory tract specimens were collected from all the subjects at enrollment and on the following 3 d. PCT assays were performed within 1 h of enrollment. Lung ultrasound and then computed tomography of the chest were performed within 24 h to detect lung consolidations. The subjects were divided into VAP and non-VAP groups according to the results of a computed tomography of the chest and semi-quantitative culture of the lower respiratory tract sample. A total of 124 subjects were included (48 in the VAP group and 76 in the non-VAP group). A positive lung ultrasound result combined with PCT of ≥0.25 ng/mL diagnosed VAP, with a sensitivity and specificity of 81.3 and 85.5%, respectively. The area under the receiver operating characteristic curve was significantly higher for lung ultrasound combined with PCT than for a white blood cell count, PCT, C-reactive protein, or Clinical Pulmonary Infection Score alone. A combination of lung ultrasound and PCT was accurate in the diagnosis of VAP. Lung ultrasound is a useful lung-imaging tool to assist VAP diagnosis.